Suppression of the Oncogenic Transcription Factor FOXM1 by Proteasome Inhibitors - Andrei L. Gartel (Scientifica)
The oncogenic transcription factor FOXM1 is one of the key regulators of tumorigenesis. We found that FOXM1 upregulates its own transcription and its protein stability depends on its interaction with the chaperone nucleophosmin. We also determined that FOXM1 is negatively regulated by the tumor suppressor p53. We identified the thiazole antibiotics Siomycin A and thiostrepton as inhibitors of transcriptional activity and FOXM1 expression via proteasome inhibition. In addition, we found that all tested proteasome inhibitors target FOXM1. We showed synergy between thiostrepton and bortezomib in different human cancer cell lines and in vivo. We generated isogenic human cancer cell lines of different origin with wild-type p53 or p53 knockdown and we demonstrated that proteasome inhibitors induce p53-independent apoptosis in these cells. Using RNA-interference or proteasome inhibitors to inhibit FOXM1 we found that suppression of FOXM1 sensitized human cancer cells to apoptosis induced by DNA-damaging agents or oxidative stress. We encapsulated thiostrepton into micelle-nanoparticles and after injection we detected accumulation of nanoparticles in tumors and in the livers of treated mice. This treatment led to inhibition of human xenograft tumor growth in nude mice. Our data indicate that targeting FOXM1 increases apoptosis and inhibits tumor growth.